The Role of Social Support in the Prevention and Recovery of Post-Traumatic Stress Disorder (PTSD) in Vulnerable Populations Following Natural Disasters: A Systematic Review and Meta-Synthesis of Empirical Studies. - Alita, Putri (CV. ARGA FARMA, 2025)
This study aims to conduct a systematic review and meta-synthesis on the role of social support in the prevention and recovery of post-traumatic stress disorder (PTSD) in vulnerable populations following natural disasters. Natural disasters can cause profound psychological impacts, particularly among vulnerable groups such as children, women, and the elderly. Social support has been shown to be an effective protective factor in reducing PTSD symptoms and accelerating psychological recovery post-disaster. This review includes 18 empirical studies published between 2000 and 2025, employing various research methods, including quantitative, qualitative, and mixed methods. The findings indicate that emotional support from family, friends, and communities plays a significant role in reducing PTSD symptoms, while social support-based therapies, such as group play therapy, have also proven effective, especially for children affected by disasters. However, despite the effectiveness of social support, significant challenges remain, including limited access to mental health services and stigma surrounding mental health issues in disaster-affected areas. This study recommends strengthening community-based social support systems and further research on the long-term impacts of social support in PTSD recovery.